KURIKULUM PENDIDIKAN JASMANI: STUDI ANALISIS KITAB TARBIYATUL AULAD FIL ISLAM - Suprayitno, Sigit; Mujahidin, Endin (Tawazun: Jurnal Pendidikan Islam, 2020)
Many boarding schools that do not have a specific physical education curriculum, which is design as a reference for educators in implementing the process of learning. In this article, the author will explore the curriculum of physical education based on the analysis of the book Tarbiyatul Aulad Fill Islam. The method used in this research is library research with the approach of content analysis. The results of this research include the physical education curriculum starting from the role of parents in providing healthy and good food, decent clothing, comfortable housing, following healthy diet rules of health, protecting themselves from infectious diseases, treating diseases, not endangering oneself and others, familiarizing exercising. The sport recommends as is; Archery, swimming, horse riding, and throwing spears, familiarizing the life of Zuhud, embedding the character of officers.ols that do not have a specific physical. Abstrak Banyak pondok pesantren yang belum memiliki kurikulum pendidikan jasmani secara khusus, yang dirancang sebagai acuan bagi para pendidik dalam pelaksanaan proses pembelajarannya. Dalam artikel ini penulis akan menggali kurikulum pendidikan jasmani berdasarkan analisis dari kitab Tarbiyatul Aulad Fill Islam. Metode yang digunakan dalam penelitian ini libray research dengan pendekatan conten analysis. Hasil penelitian ini yaitu kurikulum pendidikan jasmani dimulai dari peran orang tua dalam memberikan makanan yang sehat dan baik, pakaian layak, tempat tinggal nyaman, mengikuti aturan-aturan kesehatan pola makan sehat, memproteksi diri dari penyakit menular, mengobati penyakit, tidak membahayakan diri sendiri dan orang lain, membiasakan berolahraga. Adapun olahraga yang sangat dianjurkan seperti; memanah, berenang, berkuda, dan melempar tombak, membiasakan hidup zuhud, menanamkan karakter perwira.